The Role Of Organizational Culture to EmployeePerformance Improvement In Higher Institutions: Case Study : The University Of Pawyatan Daha - Curtinawati, Rizki Fillya (Publiciana, 2023)
Organizational Culture in Educational Institutions is the joint development of all members of the organization in an educational institution related to values, norms, beliefs, traditions beliefs, and ways of thinking that they adhere to and appear in their behavior. Therefore, building a strong organizational culture is an important agenda for educational institutions.. The focus of this research is to find out how organizational culture is in the Pawyatan Daha University environment and to find out the factors that affect employee performance. This research uses a descriptive case study approach. The results of the study show that the organizational culture in the Pawyatan University environment is low for the formal system, namely the employee's response to all rules/policies that have been set, while for the informal system it is good enough to cover communication and collaboration. And also from the external environmental system it has also been quite good by re-joining the Pawyatan Daha Central Foundation which previously used campus autonomy in administering higher education. While there are 3 factors that affect performance, namely: individuals including educational background and age, psychological including low motivation and creativity, the last is the organization, namely the presence of multiple positions for several employees and the uneven distribution of tasks and poor leadership